2020
DOI: 10.1021/acs.jpcc.0c00130
|View full text |Cite
|
Sign up to set email alerts
|

Zeolite Adsorption Isotherms Predicted by Pore Channel and Local Environmental Descriptors: Feature Learning on DFT Binding Strength

Abstract: Fast prediction of adsorption isotherms is of great importance in the structural characterization and property prediction of zeolites prior to the synthesis of the target zeolite. Here, we employ the feature learning (FL) method to simulate the adsorption isotherms through density functional theory data generation of binding strength of nitrogen molecule adsorption in zeolites. Three features, that is, the size of adsorption cavities, the geometry of the pore apertures, and the local geometric distortion, are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 58 publications
2
13
0
Order By: Relevance
“…[49][50][51][52] It has been demonstrated by our group that R DLS is one of the three important features in predicting nitrogen adsorption strength in 200 429 kinds of siliceous zeolites. 29 Here, we found that R DLS gets larger to about 0.067-0.194 in metal-zeolites than that (0.005) in siliceous zeolites due to the signicant perturbation of the zeolite framework upon coordination with metal atoms. Among all the studied systems, the introduction of Pb atoms leads to the least distortion of the zeolite framework with R DLS ¼ 0.067, due to the weak coordination strength between Pb and O atoms with distances of about 2.35-2.86 Å.…”
Section: Feature Selectionmentioning
confidence: 58%
See 3 more Smart Citations
“…[49][50][51][52] It has been demonstrated by our group that R DLS is one of the three important features in predicting nitrogen adsorption strength in 200 429 kinds of siliceous zeolites. 29 Here, we found that R DLS gets larger to about 0.067-0.194 in metal-zeolites than that (0.005) in siliceous zeolites due to the signicant perturbation of the zeolite framework upon coordination with metal atoms. Among all the studied systems, the introduction of Pb atoms leads to the least distortion of the zeolite framework with R DLS ¼ 0.067, due to the weak coordination strength between Pb and O atoms with distances of about 2.35-2.86 Å.…”
Section: Feature Selectionmentioning
confidence: 58%
“…The theoretical data of metal-zeolites contained 4428 geometry-related data, 5412 electronic-structure-related data, and 1968 reaction-related data for 492 structures with 27 metal elements, as shown in Table S2 †. As the first step of nitrogen activation, the nitrogen adsorption in various zeolites along with three features, 29 including effective adsorption space ( V eff ), pore largest diameter (PLD), and Si–O–Si refinement distance least squares ( R DLS ), is also collected in the ZA dataset.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The three-dimensional zeolite structure is composed by tetrahedron units with Si atoms in the centre and four oxygen atoms at the vertices, which can organise in a variety of porous frameworks, with pores of sizes varying between 2 and 10 nm [27,28]. ML methods coupled to DFT computations have already emerged for predicting mechanical properties [29], nitrogen adsorption [30], molar volumes, and cohesive energies [31] in zeolites. The success rate of these ML applications to zeolites vary according to the predicted properties and the proposed ML approach [32].…”
Section: Introductionmentioning
confidence: 99%